Interpersonal Forgiveness and Meaning in Life in Older Adults: The Mediating and Moderating Roles of the Religious Meaning System - Krok, Dariusz (Religions, 2021)
Forgiving others may play an important role in achieving meaning in life as it offers a valuable platform for deliberate moral acts of acceptance of positive affect, behaviour, and cognition towards a transgressor. The aim of this paper was to analyse the relationship between forgiveness and presence, and the search for meaning in life, as well as the mediating role of the religious meaning system in this relationship among older adults. A total of 205 older adults, 112 women and 93 men, participated in the study. The mean age was 72.59. The Transgression-Related Interpersonal Motivations Scale, the Meaning in Life Questionnaire, and the Religious Meaning System Questionnaire were employed in the research; revenge and avoidance revealed negative correlations with presence, whereas benevolence showed positive correlations, but not with the search for meaning in life. The religious meaning system was confirmed as a mediator in the relationships between forgiveness (revenge, avoidance, and benevolence) and both presence and the search for meaning. The findings point to the significant role played by religious beliefs and behaviour in the domain of purpose and goals. Additionally, testing the mediation and moderation effects sheds new light on the interaction of compassion- and goal-oriented mechanisms in older adults’ meaning in life.